Cost‐effectiveness of a cardiac contractility modulation device in heart failure with normal QRS duration. (29th January 2020) - Witte, Klaus; Hasenfuss, Gerd; Kloppe, Axel; Burkhoff, Daniel; Green, Michelle; Moss, Joe; Peel, Alison; Mealing, Stuart; Durand Zaleski, Isabelle; Cowie, Martin R.
Abstract: Aims: The objective of this paper is to assess whether cardiac contractility modulation (via the Optimizer System) plus standard of care (SoC) is a cost‐effective treatment for people with heart failure [New York Heart Association (NYHA) III, left ventricular ejection fraction of 25–45%, and narrow QRS] compared against SoC alone from the perspective of the English National Health Service. Methods and results: We developed a regression equation‐based cost‐effectiveness model, using individual patient data from three randomized control trials (FIX‐HF‐5 Phases 1 and 2, and FIX‐HF‐5C) to populate the majority of parameters. A series of regression equations predicted NYHA class over time, mortality, all‐cause hospitalization rates, and health‐related quality of life. We conducted the analysis in line with the National Institute for Health and Care Excellence reference case, modelling costs from an English National Health Service perspective, and considering outcomes in quality‐adjusted life years (QALYs) over a patient lifetime perspective. Our base case analysis produced an incremental cost per additional QALY of GBP22 988 (€25 750) when comparing Optimizer + SoC to SoC alone. This result was not sensitive to parameter uncertainty but was sensitive to the time horizon over which costs and QALYs were captured and the duration over which a survival benefit with Optimizer + SoC can be assumed to apply. Conclusions: Cardiac contractility modulation is likely to be cost‐effective in people with heart failure with reduced ejection fraction, NYHA III, and narrow QRS, provided that the treatment benefit can be maintained beyond the duration of the existing clinical trial follow‐up. This analysis supports the current recommendations of the European Society of Cardiology that this therapy may be considered for such patients.